Sample Avocado Production Costs and Profitability Analysis for Florida - Edward A. Evans; Sikavas Nalampang (EDIS)
FE837, a 4-page illustrated fact sheet by Edward A. Evans and Sikavas Nalampang, provides an estimate of the costs and returns associated with avocado production in Miami-Dade County and a brief analysis of the profitability of the industry. Includes references. Published by the UF Department of Food and Resource Economics, June 2010.